LRP6 regulates growth in Litopenaeus vannamei via the Wnt/β-catenin signaling pathway - Sheng Wang; Xiaodi Wang; Hao Yang; Xuanzheng Di; Haoyang Li; Bin Yin; Ziwei Liu; Chaozheng Li; Jianguo He (Aquaculture Reports)
Low-density lipoprotein receptor-related protein 6 (LRP6) is a crucial coreceptor in the canonical Wnt/β-catenin signaling pathway, that plays a fundamental role in cell growth, development, proliferation, and apoptosis. However, little is known about its effect on growth performance in economic animal including shrimp. In this study, we characterized a homolog of LRP6 in shrimp Litopenaeus vannamei, named LvLRP6, and explored its involvement in growth regulation. Multiple sequence alignments and phylogenetic analyses indicated that LvLRP6 belongs to the invertebrate LRP6 family and has conserved phosphorylation sites with those of LRP6 in other species. Functional investigations via RNAi technology revealed that silencing LvLRP6 via dsRNA injection resulted in a significant reduction in shrimp growth, as indicated by lower weight gain than that in the control group. Mechanistic exploration revealed that LvLRP6 positively modulates the Wnt/β-catenin pathway, leading to increased expression of core components such as glycogen synthase kinase 3 (LvGSK3), β-catenin (Lvβ-catenin), and T-cell factor (LvTcf). Furthermore, LvLRP6 exerted a suppressive effect on LvMSTN (myostatin), a negative regulator of muscle-related genes, while concomitantly increasing myosin levels. Subsequent research revealed that the promoter of LvMSTN contains TCF binding motifs. Dual-luciferase reporter experiments confirmed that the overexpression of LvLRP6 or LvTcf reduced the promoter activity of LvMSTN. Additionally, LvTcf was found to induce the expression of LvLRP6 and a number of Wnt ligands, thus amplifying Wnt/β-catenin pathway activation and reinforcing the growth-promoting feedback loop. The present investigation demonstrated the importance of LRP6 in shrimp growth, which contributes to our knowledge of the molecular processes that underlie crustacean growth and offers a theoretical basis for breeding and genetic enhancement initiatives aimed at enhancing shrimp aquaculture growth performance.